Perkembangan Arsitektur Kolonial Di Indonesia - Tri Prasetyo Utomo (Ornamen, 2007)
The presence of Dutch in Indonesia resulted in the acculturation between two different cultures. Colonial culture (European) and Indonesian culture, each of them is supported by different ethnic has also different social structure and encounters the long assimilation process. The convergence of two cultures leads indigenous culture (Indonesian) to encounter a significant cultural transformation, this occurs because there is colonial (European) culture’s influence entering Indonesia. The influence gradually becomes greater and the effect is widespread reaching various sectors and cultural elements. Among colonial effects evolving in Indonesia there is the effect in architecture development.Key word : architecture, Colonial